The simultaneous synthesis of hydrogen-rich gas and oxidation of fine metal particles in water vapour plasma - Valinčius, V.; Grigaitienė, V.; Valatkevičius, P.; Tamošiūnas, A. (Вопросы атомной науки и техники, 2013)
Atmospheric pressure water vapor plasma technology was developed, tested and implemented for the experimental research of fuel conversion processes. The present study offers a methodology for production of hydrogen-rich gas and additional deposition of small metal oxide dispersed particles by the employment of nonequilibrium water vapour arc plasma at atmospheric pressure. The results of the present study enables constructing a specific device which allows a highly efficient production of the synthetic gas containing an increased amount of hydrogen and its use in the production of second generation fuels. The injection of copper dispersed particles causes the oxidation and removal of dissociated oxygen and simultaneous synthesis of fine particles. The relation between the yield of hydrogen in an exhaust gaseous product, the arc current, particle material, and water vapor flow rate in the plasma torch was determined.